Integration of Participatory Action Research and Community-Led Total Sanitation in Transforming the Sanitation Behavior of Riverbank Communities Toward an Open Defecation Free Village - Fiqi Nurmanda Sari; Nurfadliyati Nurfadliyati (SWAGATI : Journal of Community Service, 2026)
Open Defecation (OD) along riverbanks constitutes a multidimensional sanitation challenge rooted in cultural normalization, limited infrastructure, and the absence of binding local regulations. This community engagement program aims to transform sanitation behavior among residents of Berembang Village, Muaro Jambi Regency, through an integrative intervention model that combines Participatory Action Research (PAR) with Community-Led Total Sanitation (CLTS). The intervention procedure comprises three sequential stages: (1) triggering and social mapping to build collective awareness and identify high-risk OD locations; (2) policy and institutional advocacy to promote the formulation of a Village Regulation draft on sanitation; and (3) a stimulus-based infrastructure intervention through the distribution of SNI-standard squat toilets to Low-Income Communities (LICs). Program evaluation was conducted using a participatory monitoring approach with data source triangulation. The results indicate: in the cultural dimension, the establishment of an anti-OD “Social Contract” reflecting a shift in social norms; in the institutional dimension, the development of a Village Regulation draft as a long-term instrument of social control; and in the physical dimension, improved access to proper sanitation for vulnerable groups through a community-based self-help (gotong royong) development model. The “Behavior Change Triangle” model—integrating software (awareness), hardware (facilities), and rules (regulations)—has proven effective as a strategy to accelerate the achievement of Open Defecation Free (ODF) status in riparian areas.